Potensi dan Tantangan Implementasi Akad Wakalah bil Ujrah pada Transaksi Bisnis Syariah Modern - Maulana, Maulana; Bin Sapa, Nasrullah; Ambo Masse, Rahman; Galib, Mukhtar (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This research aims to explore the potential and challenges of implementing Akad Wakalah bil Ujrah in modern Islamic business transactions in Indonesia. The research method used is qualitative research with a case study approach. Data was collected through in-depth interviews with Islamic finance practitioners, analysis of documents related to Islamic business regulations and transactions, and direct observation of the implementation process of Akad Wakalah bil Ujrah. The research results show that there is great potential in applying this akad to increase operational efficiency, reduce risk, and support the growth of the Islamic finance industry. However, challenges such as lack of understanding among business actors, unclear regulations, lack of supporting infrastructure, and the risk of misuse become obstacles that need to be overcome. By overcoming these challenges through educational efforts, regulatory improvements, infrastructure development, and the implementation of strict monitoring mechanisms, the implementation of Akad Wakalah bil Ujrah can be an effective instrument in supporting the growth of modern Islamic business in Indonesia